Development of efficient designs of cooking systems. III. Kinetics of cooking and quality of cooked food, including nutrients, anti-nutrients, taste, and flavor - Singhal, R.; Pandit, A.; Joshi, J.; Patel, S.; Danao, S.; Shinde, Yogesh; Gudekar, A.; Bineesh, N.; Tarade, K. (2012)
Part III of the series on cooking systems presents a qualitative description of cooking methods such as open pan cooking, pressure cooking, steam cooking, solar energy-based cooking, microwave cooking, etc. A large number of chemical and physical changes occur during the process of cooking. These changes have been comprehensively covered in published literature including some textbooks. An attempt has been made to discuss a brief coherent description regarding the changes occurring in starches, proteins, fats, etc. The kinetics of the cooking reaction has also been investigated. This information can be advantageously employed for developing a protocol for an optimum temperature-time program. Because the cooking process is practically thermally neutral, a good scope is available for the optimization of energy supply. It was also thought desirable to understand the kinetics of degradation of proteins, vitamins, anti-nutrients, and flavors in different cooking practices, including microwave ovens and pressure cookers. The mechanism of cooking of rice and lentils has been described. The cooking process involves first the transfer of water from bulk to the particle surface, where the resistance for transfer is provided by a thin film in the vicinity of grain (rice and lentils) surfaces. Second, water has to transfer from the external surface to swollen cooked mass to uncooked core. Finally, on the surface of the uncooked core, the cooking reaction occurs. All published literature regarding this mechanism has been systematically analyzed, and the procedure has been given regarding the rate controlling step(s) and the estimation of the overall rate of cooking. For this purpose, the mathematical models have been given and methods have been described for the quantitative evaluation of the model parameters. A substantial amount of additional work is needed on the mechanism of cooking and suggestions have been made for future research. © 2011 American Chemical Society.